(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
“We don’t need a handful of people doing zero waste perfectly. We need millions of people doing it imperfectly.”- Anne Marie BonneauWhile organizations at a global level are taking major steps to protect the environment through waste management initiatives, a woman at Bengaluru, through her innovative initiatives of “Swachha Graha” has influenced lakhs to join her in the art of composting. Her work and story of zero waste, zero cost and zero smell have popularly made her call composite queen. Through this case, the author under the ambit of waste management wants to underpin the relevance of making a lifestyle change and suggests following a methodical step at home to practice this concept of zero waste. This paper delineates all those steps and techniques that Mrs.Vani Murthy uses to produce the manure. From inception to its final disposal, she highlights that one needs to understand the process, understand the eco-system. Dry leaves, rotten food, vegetable peel, leftover food, all are collected and treated with buttermilk as a microbe catalyst and mixed well until earthworms start to appear and participate in breaking down the organic matter turning the whole thing into compost within 35 to 45 days. Her rich garden, green leafy vegetables, kitchen herbs and green grass are all products of her homemade composite that she boasts with humbleness in her webinars and training sessions. She accentuates that this “Art of Composting” must be learned by all for making one’s home as “Swachha Graha”.For writing this case, the author relied on secondary data available on the internet search, mainly her videos, newspaper and online articles. A thorough study of her works, their interpretation and paraphrasing enabled the author to suggest a waste management model, postulate the guidelines for waste management at home and propose scope for further research in this promising area for generating more awareness amidst the masses.